Effect of β-mannanase enzyme supplementation on the morphofunctional state of broiler chickens’ immunocompetent organs - A. V. Oliyar; P. M. Skliarov; D. M. Masiuk; D. D. Bilyi; V. V. Logvinova; M. A. Lieshchova (Regulatory Mechanisms in Biosystems, 2020)
Identifying and eliminating factors that interfere with the nutrient absorption from feed is essential for successful poultry rearing. The nutritional value of feed mixtures used in the poultry industry can be increased by the use of enzyme supplements, in particular β-mannanase (Hemicell), which breaks down the anti-nutrients β-mannans that are present in significant quantities in soy products. For the study, two groups of 50 broiler chickens were formed. In the control group a standard feed mixture from cereals was used, particularly soybeans, and in the experimental group 0.05% β-mannanase enzyme supplement (Hemicell) in addition to the compound feed was used. Production indicators were established (average daily gain, survival rate, feed costs). On the 15th, 25th and 42nd days of rearing, lymphatic organs (cloacal bursa and spleen) were collected from seven chickens of each group, followed by macro, microscopic and morphometric evaluation. It was found that the addition of an enzyme supplement promotes an increase in the production indicators of poultry rearing, reduces feed use, does not affect the macroscopic characteristics of the lymphatic organs. β-mannanase (Hemicell) contributes to the maintenance of an active morphofunctional state of the cloacal bursa and spleen during the entire period of poultry rearing. This was manifested by high indices of the absolute and relative organ masses, a moderate development degree of tissue components and cloacal bursa histological structures (number, shape and average length of lymphatic nodules, density of lymphocytes in the cortex and medulla) and spleen (number and diameter of lymphatic nodules and periarterioal lymphatic sheaths). In the control group, at all stages of rearing, the morphofunctional state of the bursa was found to be lower and signs of immunosuppression were revealed by the end of the rearing period (a sharp decline in the bursa absolute mass, organ mass index, a decrease in the average length of nodules, change in their shape, thinned cortical layer and delymphotisation). The morphofunctional state of the spleen of chickens from the control group remained high throughout the entire study period. So use of the β-mannanase enzyme supplement (Hemicell) while rearing broiler chickens not only increased the efficiency of their rearing but also contributed to maintaining a high morphological and functional state of the cloacal bursa.